(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In post soviet countries the problems of migration acquired special importance due to following circumstances. Social changes over the past two decades have dramatically changed the political and social situation in the Kazakh society and millions of people were displaced migrants. Kazakhstan faces intense migratory flows in an environment where its economic base was in a state of crisis. For example, illegal migration, the outflow of professionals, not balanced location of migrants in the country, increasing competition in the labor market, etc. – all this affects to the national security and social stability, which require immediate solution. Key words: migration, internal migration, external migration, oralmans, migrants, returnees, illegal migration, labor migration..